Decreased native T1 values and Impaired myocardial contractility in anabolic steroid users - de Souza, F. R.; dos Santos, M. R.; Rochitte, C. E.; dos Santos, R. P.; Jordão, C. P.; Leite, I. S.; da Fonseca, G. W. P.; Fonseca, R. A.; de Oliveira, T. F.; Yonamine, M.; Pereira, R. M. R.; Negrão, C. E.; et al. (International Journal of Sports Medicine, 2022)
Anabolic androgenic steroid (AAS) abuse leads to myocardial toxicity. Human studies are conflicting about the myocardial fibrosis in AAS users. We evaluated cardiac tissue characterization, left ventricle (LV) function, and cardiac structure by cardiovascular magnetic resonance (CMR). Twenty strength-trained AAS users (AASU) aged 29±5 yr, 20 strength-trained AAS nonusers (AASNU), and 7 sedentary controls (SC) were enrolled. Native T1 mapping, late-gadolinium enhancement (LGE), extracellular volume (ECV), and myocardial strain were evaluated. AASU showed lower Native T1 values than AASNU (888±162 vs. 1020±179 ms p=0.047). Focal myocardial fibrosis was found in 2 AASU. AASU showed lower LV radial strain (30±8 vs. 38±6%, p<0.01), LV circumferential strain (-17±3 vs. -20±2%, p<0.01), and LV global longitudinal strain (-17±3 vs. -20±3%, p<0.01) than AASNU by CMR. By echocardiography, AASU demonstrated lower 4-chamber longitudinal strain than AASNU (-15±g3 vs. -18±2%, p=0.03). ECV was similar among AASU, AASNU, and SC (28±10 vs. 28±7 vs. 30±7%, p=0.93). AASU had higher LV mass index than AASNU and SC (85±14 vs. 64±8 vs. 58±5 g/m2, respectively, p<0.01). AAS abuse may be linked to decreased myocardial native T1 values, impaired myocardial contractility, and focal fibrosis. These alterations may be associated with maladaptive cardiac hypertrophy in young AAS users.